2019
DOI: 10.1590/2237-6089-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Iranian version of the Anxiety Sensitivity Index-3 (ASI-3)

Abstract: Introduction: Anxiety sensitivity plays a prominent role in the etiology of anxiety disorders. This construct has attracted widespread interest from experts and researchers. The Anxiety Sensitivity Index (ASI-3) is the most common scale for measuring anxiety sensitivity. Objective: To analyze the psychometric properties and factor structure of the ASI-3 in Iranian student samples. Methods: 220 students (135 women, 85 men) from Kermanshah University of Medical Sciences were selected by the convenience samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The physical and cognitive subscales were used for the current study. The Farsi version of the questionnaire has been used in several previous studies and has been demonstrated to be a valid and reliable measure [Cronbach's alpha = 0.90, (26)]. Cronbach's alpha in the current sample was = 0.91.…”
Section: Anxiety Sensitivity Index (Asi-3)mentioning
confidence: 85%
“…The physical and cognitive subscales were used for the current study. The Farsi version of the questionnaire has been used in several previous studies and has been demonstrated to be a valid and reliable measure [Cronbach's alpha = 0.90, (26)]. Cronbach's alpha in the current sample was = 0.91.…”
Section: Anxiety Sensitivity Index (Asi-3)mentioning
confidence: 85%
“…However, many studies have confirmed the three-related factor model for the factor structure of the ASI-3, as suggested by Taylor et al. (2007) (Foroughi et al., 2019; Kemper et al., 2012; Petrocchi et al., 2014; Wheaton et al., 2012). Although the results of the three-related factor models in this study can be interpreted as acceptable, the bifactor model gives the best-fit indices.…”
Section: Discussionmentioning
confidence: 76%
“…Scholars examined the structure of the ASI-3 on clinical and non-clinical samples, and tested the accuracy of the three-factor hierarchical model determined by Taylor et al. (2007) (Cai et al., 2018; Foroughi et al., 2019; Kemper et al., 2012; Petrocchi et al., 2014, Wheaton et al., 2012). However, in some studies where the hierarchical model was determined to fit the data, this result differed slightly from the original study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the internal consistency of the ASI score was 0.95. Foroughi et al (23) reported an alpha Cronbach coefficient of 0.90 for the tool.…”
Section: Anxiety Sensitivity Indexmentioning
confidence: 99%